Effect of long-term rice straw incorporation on soil phosphorus availability in a sandy loam soil - KAUR, MANDEEP; SAINI, SAT PAL (Journal of Soil and Water Conservation, 2020)
A field experiment was conducted on a sandy loam soil at Ludhiana to investigate the effect of longterm rice straw incorporation (0-10 t ha-1 yr-1) and fertilizer N (0-150 kg N ha-1) application on soil phosphorus fractions. The treatments were arranged in a split plot design with three replications, with fertilizer N (N0, N90, N120 and N150) in main plots and rice straw (RS0, RS5, RS7.5 and RS10) in sub-plots. Rice straw incorporation (RS7.5) significantly (p